2020
DOI: 10.1155/2020/4014512
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Anterior Chamber Angle and Intraocular Pressure Early after V4c Implantable Collamer Lens Implantation

Abstract: Purpose. To confirm the relationship between anterior chamber angle (ACA) and intraocular pressure (IOP) early after V4c implantable collamer lens (ICL) implantation. Methods. Patients were assigned to two groups: (1) right eyes (control group) and (2) left eyes (experimental group), with miosis conducted immediately after ICL implantation in the left eyes. IOP, angle opening distance (AOD), trabecular-iris angle (TIA), and pupil diameter (PD) were compared between two groups at postoperative hours 1, 2, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…High intraocular pressure and secondary glaucoma High intraocular pressure and secondary glaucoma account for 4.4% of postoperative complications after ICL implantation [136], and the causes include steroid response, viscoelastic agent residue, aqueous misdirection, pupillary block, Iris pigmentation, narrow ACA, etc. [137][138][139]. The increase in IOP mostly reached its peak at the end of the first postoperative month, and the vast majority of patients can resume normal IOP [137].…”
Section: Loss Of Corneal Endothelial Cells and Corneal Decompensationmentioning
confidence: 99%
“…High intraocular pressure and secondary glaucoma High intraocular pressure and secondary glaucoma account for 4.4% of postoperative complications after ICL implantation [136], and the causes include steroid response, viscoelastic agent residue, aqueous misdirection, pupillary block, Iris pigmentation, narrow ACA, etc. [137][138][139]. The increase in IOP mostly reached its peak at the end of the first postoperative month, and the vast majority of patients can resume normal IOP [137].…”
Section: Loss Of Corneal Endothelial Cells and Corneal Decompensationmentioning
confidence: 99%
“…Hu et al found that early increase in IOP after V4c model implantation was associated with a narrowed anterior chamber angle and higher pupil diameter. 68 They recommended the use of intracameral miotics immediately after the operation to reduce the incidence of early postoperative increase in IOP. Persistent IOP elevation after ICL implantation in hole-ICL models is rare.…”
Section: Resultsmentioning
confidence: 99%
“…15,23,24 Other studies enrolling different ethnical groups, particularly Chinese and Japanese individuals, have reported preoperative TIA values ranging from 40.0 to 58.4 degrees. 17,25–28 Lim et al reported a mean preoperative TIA of 31.9 degrees, which reflects the association between the ACA and the ACD, in patients with ACD lower than 2.8 mm (the minimum ACD recommended by the manufacturer). 29 In the present study, the TIA 750 correlated positively with the corneal sagittal height ( R = 0.534) and the ACD ( R = 0.503) and negatively with the CLR ( R = −0.433).…”
Section: Discussionmentioning
confidence: 99%